Empirical Study on Financial Knowledge among High School Students in Veracruz - Moreno-Garcia, Elena; Garcia-Santillan, Arturo; Navarrete, Daniel Martinez (International Journal of Innovative Research and Scientific Studies, 2022)
The financial knowledge that young people have is fundamental to their financial decision making, to guarantee their future consumption and their well-being in retirement. The study focused on analyzing the knowledge that high school students have of income, money management, savings, investment, credit and spending, and comparing if there is a difference by gender. Data from 100 high school students from Boca del Río, Veracruz were obtained using test designed by Contreras-Rodríguez, et al. The analysis seeks to determine the structure of variables that explain the knowledge that Mexican high school students have of financial topics; in addition to verifying that the variables are correlated and that the data matrix is not an identity matrix. The results show that the instrument used has a relatively low Cronbach's alpha (0.597). It was verified that the data matrix did not constitute an identity matrix, which made the data analysis possible through factorial analysis with component extraction. The two extracted factors are explained by 67% of the total variance. The ANOVA tests and the values of the F statistic with gl and its significance (0.05), as well as the Levene statistic, showed that there is no gender difference. Based on the results, strengthening financial education of students is advisable to contribute to their future inclusion in the financial system.